Synopse des lois du Pentateuque - Lasserre, Guy, 1958- (Supplements to Vetus Testamentum,, 1994)
Synopse des lois du Pentateuque contains synopses in Hebrew of the different laws of the Pentateuch arranged thematically. The main collections and lists are followed in succession and in their entirety. The main part of the work consists of the synopses. The laws figure in them according to the collections and lists to which they belong. Secondary parallels indicate allusions to or quotations from the Old Testament. The introduction gives the methodological principles of the work and explains how to use it. Tables enable the student to visualise all the parallels quickly. Notes explain the choices that have been made. In order to study the laws, it is essential to compare them. This book facilitates research into the pentateuchal collections and lists, as it does into special prescriptions, rites or institutes.